Tin-bearing magnetite with nanoscale Mg-Si defects: Evidence for the early stages of mineralization in a skarn system - Xu, Jing; Ciobanu, Cristiana L.; Cook, Nigel J.; Slattery, Ashley D.; Ehrig, Kathy; Wade, Benjamin P.; Courtney-Davies, Liam; Wang, Liyuan (Frontiers in Earth Science, 2023)
Tin-bearing magnetite is reported from several types of magmatic-hydrothermal ore deposits. The question of whether tin is incorporated within solid solution, as Sn4+, or as nanoinclusions remains open, however. We report a micron- to nanoscale investigation of Sn (Mg, Si)-bearing magnetite from serpentinite in the Dulong Zn-Sn-In skarn, South China, with the dual aims of understanding the mechanisms involved in accommodating Sn and associated elements into the Fe-oxide, and the inferences that this carries for constraining the early stages of skarn formation. Magnetite preserves a range of textures that record the evolution of metasomatism during prograde growth of grain cores and retrograde rim replacement. Observations reveal the presence of chondrodite and sellaite (MgF2) as nanoscale inclusions preserved in magnetite. This implies initiation of the Dulong mineralizing system during a humite-bearing, magnesium skarn stage. Magnesium-Si defects, forming along (110) planes prior to Sn-enrichment, are recognized for the first time. Release of high volatile, F-rich fluids is interpreted to lead to precipitation of cassiterite inclusions along <111*> directions in magnetite.